Green Lending in the Age of AI: Rethinking Risk and Opportunity in Lebanon’s Banking Sector - Sayegh, Nancy (Global journal of Business and Integral Security, 2026)
In recent years, the concept of AI-enabled green lending has been progressively gaining popularity as an innovative tool to promote sustainable finance and achieve environmentally-friendly objectives in the banking industry. Using a quantitative approach with a survey, a hundred experts in the field were surveyed to examine their opinions on readiness, risks, and opportunities concerned with AI-enabled green lending in Lebanese banks. The results showed that there is a moderate AI readiness and optimism concerning opportunities with independent concerns related to risks like regulatory uncertainty, data privacy, and algorithmic bias. The results also showed that drivers like economic incentives and ESG compliance statistically outweighed barriers, with participants’ role and experience playing a significant part in the outcomes.